Content-Based Information Retrieval and Digital Libraries - Wan, Gary (Gang); Liu, Zao (Information Technology and Libraries, 2008)
This paper discusses the applications and importance of content-based information retrieval technology in digital libraries. It generalizes the process and analyzes current examples in four areas of the technology. Content-based information retrieval has been shown to be an effective way to search for the type of multimedia documents that are increasingly stored in digital libraries. As a good complement to traditional textbased information retrieval technology, content-based information retrieval will be a significant trend for the development of digital libraries.